Brand - Extension Price Premium : An Enquiry on the Role of Perceived Fit Among Users of a Consumer Durable in India - Joji Alex, N.; Varghese, Aneesh (Indian Journal of Marketing, 2016)
Purpose : The objective of this study was to ascertain the association between perceived fit and the brand extension price premium. It further studied the moderating role of performance risk, financial risk, and social risk on the association between fit and brand extension price premium. Design : The sample consisted of a total of 335 respondents who were existing users of Sony (registered trademark) LCD TV. The related brand extension product was an advanced 3D Sony LED TV and the unrelated brand extension product was Sony wet and dry vacuum cleaner (fictitious product), whose fair prices were quoted based on competitor market prices. The comparable prices and features were explained to the respondents for both the products. Findings: The hypothesis (H1), fit leads to an increase in brand extension price premium, was accepted for both related and unrelated extensions. The hypothesis (H2), for the extension category, the financial risk positively increases the effect of fit on brand extension price premium, is rejected. The hypothesis (H3), for the extension category, the performance risk positively increases the effect of fit on brand extension price premium, is accepted for both related and unrelated extension. The hypothesis (H4), for the extension category, the social risk positively increases the effect of fit on brand extension price premium, is accepted for both related and unrelated extension. The main effect of financial, performance, and social risks was not directly significant in determining the price premium of product brand extensions. Originality/Value : The respondents of this study were actual users of a brand unlike the previous study which was conducted using an experimental design among students. It also looks into the external validity from an Indian context.